Research trends in cardiovascular tissue engineering from 1992 to 2022: a bibliometric analysis - Lai, Ping; Sheng, Ming; Ye, Jin-hua; Tang, Zhi-xian; Hu, Shuo; Wang, Bei; Yuan, Jing-lin; Yang, Yi-hong; Zhong, Yi-ming; Liao, Yong-ling (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiovascular tissue engineering (CTE) is a promising technique to treat incurable cardiovascular diseases, such as myocardial infarction and ischemic cardiomyopathy. Plenty of studies related to CTE have been published in the last 30 years. However, an analysis of the research status, trends, and potential directions in this field is still lacking. The present study applies a bibliometric analysis to reveal CTE research trends and potential directions. Methods On 5 August 2022, research articles and review papers on CTE were searched from the Web of Science Core Collection with inclusion and exclusion criteria. Publication trends, research directions, and visual maps in this field were obtained using Excel (Microsoft 2009), VOSviewer, and Citespace software. Results A total of 2,273 documents from 1992 to 2022 were included in the final analysis. Publications on CTE showed an upward trend from 1992 [number of publications (Np):1] to 2021 (Np:165). The United States (Np: 916, number of citations: 152,377, H-index: 124) contributed the most publications and citations in this field. Research on CTE has a wide distribution of disciplines, led by engineering (Np: 788, number of citations: 40,563, H-index: 105). “Functional maturation” [red cluster, average published year (APY): 2018.63, 30 times], “cell-derived cardiomyocytes” (red cluster, APY: 2018.43, 46 times), “composite scaffolds” (green cluster, APY: 2018.54, 41 times), and “maturation” (red cluster, APY: 2018.17, 84 times) are the main emerging keywords in this area. Conclusion Research on CTE is a hot research topic. The United States is a dominant player in CTE research. Interdisciplinary collaboration has played a critical role in the progress of CTE. Studies on functional maturation and the development of novel biologically relevant materials and related applications will be the potential research directions in this field.